INCORPORATING LINGUISTIC LANDSCAPE INTO ENGLISH WORD-FORMATION TASK IN AN ENGLISH MORPHOLOGY COURSE - Kweldju, Siusana (TEFLIN Journal, 2021)
This exploratory case study focuses on the development and implementation of a task called the Inventive English Word Formation in Public Spaces for an undergraduate English Morphology course within the English Language Education program of a university in Indonesia. This task was created based on students' feedback that they disliked the typical memory-based test, which was reported to have a significant strain on them. In that regard, this task was developed to replace the teacher's lectures and achievement test to increase students' learning engagement and understanding of the Word Formation theory. Students were asked to morphologically analyze how Indonesian people invented new English words in commercial signs in linguistic landscapes. Sixty students were involved in the task and they were put into groups of four. Each group was assigned to write a paper reporting how they identified and explained the types and subtypes of word-formation of the invented names. The findings suggested that although students found that the task was more meaningful and engaging than the usual learning procedure, the papers they produced showed that they were still not ready for the demand of academic reading and research skills associated with the task. This task, however, promises positive avenues that can be improved and explored in future studies.